Simulation model of 3D liquid slosh in a partially filled cylindrical tank - Hussain Shah, Qasim; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
Most of the previous studies on fluid slosh within tanks have considered two-dimensional (2D) flows [I]. When a tank is excited at a frequency near the resonance, the swirling motion may be induced and superimposed on the normal slosh motion, which cannot be adequately captured by the 2D model. The laboratory experiments performed on a scale model tank will clearly shows the presence of 3D fluid slosh even under excitations along a single axis. Moreover, highway tanks comnionly encounter simultaneous excitations along all axes, which would cause 3D slosh. Only a few studies have reported the 3D slosh analysis for very limited parameters. Thus, the 3-D slosh behavior in tanks has not been well understood